MENINGKATKANPENGETAHUAN GURU SEKOLAH DASAR DALAM MENULIS ILMIAH - Sri Hapsari Wijayanti (Universitas katolik Musi Charitas, 2018)
One of the ways of teachers professionalism is they have a competency for academic writing, especially class action research (CAR). Teachers in three elementary schools, SDN Kedokan, SDN Cibogo, and SDN Mekar Wangi, at Cisauk, Tangerang, West Java, faced obstacles to write the result of CAR because they still don’t understand how to write. Besides that, they have no spirit raise their promotion because, according to them, very difficult to fulfill the requirements. The aim of this activity is giving a training about academic writing for them. The activity began with the pretest to know their knowledge of academic writing. Training used a tutorial method, discussion, writing practice, and simulation around six hours, a day. After training, the teachers have given posttest. The result of this activity indicates that teachers have an increase of knowledge in the middle level.